Projeto investigativo interdisciplinar conexão delta e as potencialidades do ensino por investigação no ensino médio - Persich, Gracieli Dall Ostro (2017)
Inquiry-based learning is a strategy that aims to promote the development of cognitive abilities in teaching-learning of scientific concepts, promoting the construction of conceptual, attitudinal and procedural knowledge that permeate the understanding of nature of science. This presupposes essential characteristics of the inquiry-based activities that aim to reach the goals of the dcientific literacy, having as means and ends the citizen education. The inquiry-based learning facilitates teaching-learning through observation, manipulation and experimentation, while it motivates and stimulates reflection, discussion, explanation, contemplating characteristics of scientific investigations. To mediate science education through projects reveals that the school function goes beyond the propaedeutics, looking for approximations with the students' identity in the way of contextualization. It shows the need to teach and learn in an integrated, non-fragmented or distant way of the problems experienced by students, because it considers what happens outside of school. Faced with this, we find interdisciplinarity as an integrating axis of curricular policies that guide High School: National Pact for Strengthening High School and National Curricular Parameters for High School. The indications of these public policies suggest that interdisciplinarity, contextualization and investigative teaching can be organized in research projects. This work presents results of the investigative project Conexão Delta, with interdisciplinary approaches in Biology, Geography, History, Integrated Seminar and Sociology, carried out by High School students of a state public school in Santo Ângelo (RS). The main goal of the project was to develop activities that collaborate with science education through innovative and differentiated methodologies, with low-cost laboratory practices, using information and communication technologies for the contextualized study of water resources. We produced a sequence of investigative teaching that guided the steps of the development of activities. We analyzed students' responses to a questionnaire to understand how they rated their involvement and their opinions about activities. The results are consistent with the proposition that inquiry-based teaching activities involve and interest students because they present an alternative to traditional teaching methodologies. Students feel an important part of the teaching-learning process and engage in activities that involve the contextual study of reality. When we reflect the functions of school beyond the instruction of contents, we think that scientific teaching must be permeated by senses, because the understanding of concepts allows the understanding of everyday phenomena to broaden the interpretation of the world. We defend the research activities organized in projects with interdisciplinary approaches for students to participate actively as constructors of the practices and protagonists of the investigations, using the knowledge produced in an autonomous and flexible way in the path of emancipation. Thus, it promotes scientific learning beyond the learning of concepts, favoring scientific literacy, environmental education and understanding of the nature of science.